PROBLEMS OF PROFESSIONAL EDUCATION IN RUSSIA: QUALITY MONITORING OF EDUCATIONAL PROGRAMS - Logachev, Maxim; Zhukova, Galina (Revista Inclusiones, 2019)
The introduction of complex management systems in educational organizations is very expensive, often without taking into account the specifics of the organization and causing the need to install and adapt additional software and hardware. Such utilities, as a rule, are cheaper and consider the possibility of step-by-step input of separate subsystems and their modification, providing means for considering the available experience of creation and operation of separate subsystems. All this is aimed at supporting the educational process but does not take into account the assessment of the preparation quality for the implementation of the educational process itself. The main element of such preparation is the formation of educational programs.